If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(8 + -3t) = 5(2 + t) (8 * 4 + -3t * 4) = 5(2 + t) (32 + -12t) = 5(2 + t) 32 + -12t = (2 * 5 + t * 5) 32 + -12t = (10 + 5t) Solving 32 + -12t = 10 + 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 32 + -12t + -5t = 10 + 5t + -5t Combine like terms: -12t + -5t = -17t 32 + -17t = 10 + 5t + -5t Combine like terms: 5t + -5t = 0 32 + -17t = 10 + 0 32 + -17t = 10 Add '-32' to each side of the equation. 32 + -32 + -17t = 10 + -32 Combine like terms: 32 + -32 = 0 0 + -17t = 10 + -32 -17t = 10 + -32 Combine like terms: 10 + -32 = -22 -17t = -22 Divide each side by '-17'. t = 1.294117647 Simplifying t = 1.294117647
| n^2006+2n^2007=3 | | 2(b+5)=3(b-7) | | x^2*123+x^2= | | 7x-9=4x+24 | | -4(2p+4)-12=2(3p+7) | | 3(2m-1)=m+7 | | 4p^2-2p=0 | | 2-y=18 | | 2x-9+1.5+6=32 | | x+(x+22)+180+x+(x+22)=720 | | P(x)=x^3-x^2-x-2 | | 7x-9=4x+25 | | 7m-8=5m+2 | | q-1.7=3.5 | | 7z+13=6z+8 | | -25=3+4y | | x^4+2x^3-6x^2=12 | | y+5=-2x(x-1) | | 2f+6=11f-12 | | 4-c=13 | | n^2006+n^2007=3 | | 118-7x=38x+18 | | 3/5+b=2/5 | | 22x+5-10x-4= | | 26p+12-21p=10+6p+11 | | 5x+-3+-4+2x=17x+-8-1 | | -6(4p+4)-36=2(5p+4) | | 13-8x=158-43x | | 7x+9y=10 | | 5x-3-4+2x=17x-81 | | 6-8x-34=14-3x+5x-2 | | -(-36)= |